Plastičnost in bolečina - Bajrović, Fajko (Rehabilitacija (Ljubljana), 2012)
The peripheral and central neural networks that mediate nociception and its modulation show extensive plasticity in pathological pain. Disease induced plasticity can occur at both functional and structural level and it is manifested as changes in individual molecules, synapses, cellular function andnetwork activity. Here we review the functional and structural plasticity of the nociceptive pathways and systems for pain modulation in the central nervous system.
Keywords: bolečina; fiziologija; neurology; nevrologija; osrednjen živčevje